Agricultural Restructure Policy in Vietnam and Practical Application for Sustainable Development in Agriculture. (17th September 2021) - Ngoc, Vinh Bao; Hung, Nguyen Manh; Pham, Phuong Thu
Abstract : The Vietnam's agricultural sector had to challenge with its course and learned lessons of further development. Novel policy might be adopted to encourage the private investments and sectors in agriculture. Furthermore, an introduction of new models such as climate-smart or green agriculture and application of modern technology increased productivity at the same time and creating jobs for millions of agricultural workers and reversing the massive rural-urban migration flux. Vietnam's agricultural sector needs to maintain the reform momentum, particularly liberalization policy, and to boost up agricultural potential. Obstacles such as land limitation policy must be removed to enable large-scale production and encourage private investment in the agricultural sector. To avoid being trapped by its own success, Vietnam is now shifting the old development paradigm that focuses too much on the quantity to the quality of the agricultural production. The government makes major efforts to achieve at the same time agricultural growth, better livelihood of the farmer, and the development of the rural areas. However, Vietnam still needs to prepare a "transition strategy" to overcome the impact of the technological progress on the traditional agricultural workers.